Comparative study of the phenolic composition and antioxidant and antibacterial activities of industrialized and artisan teas - Piza, Wellington Alves (2021)
The demand for natural foods with biological activities has been growing more and more in the world. In this context, teas are considered the most consumed beverages worldwide because of their phytochemical compositions and biological activities. The present work aimed to evaluate and compare the phenolic composition and antioxidant and antibacterial activities of industrialized and artisanal teas of Camellia sinensis, Peumus boldus and Ilex paraguariensis. The infusions were prepared by adding 100 mL of distilled water at 100 ºC over 1 g of the herb at room temperature for 10 minutes. The analysis of total phenolic compounds was performed using the Folin-Ciocalteau method. For the analysis of antioxidant activity, the DPPH free radical scavenging method was used, and the results were expressed as a percentage of scavenging. For the analysis of antibacterial activity, the agar diffusion method against Staphylococcus aureus and Escherichia coli was used. The sample with the highest phenolic content was the industrialized version of green tea, followed by the industrialized version of boldo tea and artisanal green tea, which did not differ statistically. Artisanal green tea presented the greatest antioxidant activity, followed by its industrialized version. As for antibacterial activity, there was no inhibition halo. Due to its higher phenolic content, industrialized teas are a promising option for consumers, however, more research is needed to highlight the compounds of these products, in addition to analyzing other biological activities.